Enteral Feeding Therapy for Maintaining Remission in Crohn's Disease: A Systematic Review. (8th December 2015) - El‐Matary, Wael; Otley, Anthony; Critch, Jeff; Abou‐Setta, Ahmed M.
Abstract : Background: The efficacy of enteral nutrition (EN) for maintaining remission in patients with inactive Crohn's disease (CD) is unclear. The aim of this article was to systematically identify, review, and critically appraise the evidence on efficacy of EN in maintaining medically induced remission in CD. Materials and Methods: Several databases were searched from inception to April 2015 for relevant citations of published randomized controlled trials and nonrandomized cohort studies. Two reviewers independently selected studies for inclusion and assessed study quality and risk of bias. The primary outcome was relapse rate in patients with inactive CD who have been in medically induced remission and subsequently started or maintained on EN. Results: Twelve studies (1169 patients, including 95 children) fulfilled the inclusion criteria. As the included studies were significantly heterogeneous, a meta‐analysis was not performed. Eleven studies showed that EN was either better than, or as effective as, the comparator in maintaining remission in patients with inactive CD. No major EN‐related adverse events were reported. Only 1 adult randomized controlled trial (n = 51), with low risk of bias, compared EN with regular diet and found a relapse rate of 34% in the EN group versus 64% in the control group ( P < .01) after a mean follow‐up of 11.9 months. Conclusions: EN is more effective than regular diet and as effective as some medications in maintaining remission for patients with inactive CD. Large, properly designed randomized controlled studies of sufficient duration are required to confirm this conclusion for EN versus individual medications.